The Impact of Assessment for 21st Century Skills in Higher Education Institutions: A Narrative Literature Review: - Chiva Long; Rany Sam; Chanthy Ny; Chanpheakdey Chhang; Reaksa Ren; Channy Ngork; Rika Sorn; Mary Sorn; Chhim Sor (MultiTech Publisher, 2024)
This review examines the impact of assessing 21st-century skills, such as critical thinking, communication, collaboration, and creativity, in higher education institutions. Through a narrative analysis of recent literature, the study identifies diverse assessment methodologies and their effectiveness in fostering skill development. Findings suggest that while innovative assessment practices can enhance skill acquisition, challenges remain in aligning these practices with traditional educational frameworks. The review highlights the necessity for institutions to adopt a holistic approach that integrates 21st-century skill assessment into curriculum design and pedagogy. It concludes with recommendations for educators to embrace flexible, competency-based assessments and for policymakers to support the development of frameworks that recognize and reward the acquisition of 21st-century skills. This study underscores the importance of evolving assessment practices to prepare students for the demands of the modern workforce, suggesting directions for future research in optimizing assessment strategies for 21st-century skills in higher education.